Community assessment techniques and the implications for rarefaction and extrapolation with Hill numbers. Issue 24 (21st November 2017) - Cox, Kieran D.; Black, Morgan J.; Filip, Natalia; Miller, Matthew R.; Mohns, Kayla; Mortimor, James; Freitas, Thaise R.; Greiter Loerzer, Raquel; Gerwing, Travis G.; Juanes, Francis; Dudas, Sarah E.
Abstract: Diversity estimates play a key role in ecological assessments. Species richness and abundance are commonly used to generate complex diversity indices that are dependent on the quality of these estimates. As such, there is a long‐standing interest in the development of monitoring techniques, their ability to adequately assess species diversity, and the implications for generated indices. To determine the ability of substratum community assessment methods to capture species diversity, we evaluated four methods: photo quadrat, point intercept, random subsampling, and full quadrat assessments. Species density, abundance, richness, Shannon diversity, and Simpson diversity were then calculated for each method. We then conducted a method validation at a subset of locations to serve as an indication for how well each method captured the totality of the diversity present. Density, richness, Shannon diversity, and Simpson diversity estimates varied between methods, despite assessments occurring at the same locations, with photo quadrats detecting the lowest estimates and full quadrat assessments the highest. Abundance estimates were consistent among methods. Sample‐based rarefaction and extrapolation curves indicated that differences between Hill numbers (richness, Shannon diversity, and Simpson diversity) were significant in the majority of cases, and coverage‐based rarefaction and extrapolation curves confirmed that these dissimilarities were due to differences between the methods, not the sample completeness. Method validation highlighted the inability of the tested methods to capture the totality of the diversity present, while further supporting the notion of extrapolating abundances. Our results highlight the need for consistency across research methods, the advantages of utilizing multiple diversity indices, and potential concerns and considerations when comparing data from multiple sources. Abstract : Diversity estimates play a key role in ecological assessments and are commonly used to generate complex indices that are dependent on the quality of these estimates. To determine the ability of substratum community assessment methods to capture species diversity, we evaluated four assessment methods and Hill numbers. We then conducted a method validation at a subset of locations to serve as an indication for how well each method captured the totality of the diversity present.